Audit Quality Improvement and the Role of Risk: Audit as a Moderator - Edy Sujana; Nyoman Ari Surya Dharmawan (Australasian Accounting, Business and Finance Journal, 2023)
The audit process used by the auditor directly impacts audit quality. The auditor's attitude and cognitive abilities are crucial for finishing the Audit and play a significant part in the decision-making process. Different auditing techniques and procedures can also be adjusted to situations that are not typical. Hence, additional research needs to be done on audit quality to maintain it at a high level in the future under all circumstances. This study investigates how audit quality affects the moderating factors of audit skepticism, planning, and Risk. In this study, 265 Indonesian auditor respondents served as the sample. A quantitative strategy that is put to the test via path analysis is a research method. The SmartPLS 3 testing tool was used to conduct statistical testing. The findings indicated that professional Skepticism impacted audit quality. Moreover, Audit Planning affects the quality of the Audit. It has been demonstrated that audit risk strengthens the link between professional Skepticism and audit quality. The association between audit planning and audit quality is not strengthened because audit risk produces various outcomes. As a result, the auditor must adjust for audit risk and consider it when preparing the Audit. It tries to raise the caliber of audits. The usage of information technology, which plays a significant role in the audit process, might be considered in a future study.
Keywords: Audit Quality; Audit Risk Skepticism Audit; Audit Planning